NUTRITIONAL STATUS OF INFANTS BASED ON FREQUENCY AND DIETARY DIVERSITY OF COMPLEMENTARY FEEDING - Estin Puspaningrum; Sri Umijati; Sri Utami; Dominicus Husada (UNIVERSITAS AIRLANGGA, 2020)
AbstractBackground: In 2017, the prevalence of malnutrition in Indonesia was ranked 4th among Southeast Asia countries. The nonoptimal complementary feeding is one of the reasons. The nonoptimal complementary feeding is associated with the prevalence of underweight and stunting in the children at the age 6-23 months. Complementary feeding pattern include frequency and dietary diversity. This study aims to investigate the relationship between complementary feeding pattern and nutritional status of infants at the age 7-12 months in the Kedungwaru Health Center, Tulungagung. Methods: This study used observational analytic and cross-sectional study design. The sample consisted of 71 mothers of the infants which were taken by total sampling. The variables of this study were complementary feeding pattern and nutritional status. This study also used a questionnaire and observation sheet. The Fisher Exact Test was used to analyse the data. Result: The results showed 88.7% of the infants have good nutritional status. There are 49.3% appropriate complementary feeding and 69% which applied various types of complementary feeding. The frequency of complementary feeding with the nutritional status of infants obtained p value 0.478 and the dietary diversity of complementary feeding with nutritional status obtained p value 0.102. Conclusions: There were no significant relation between the complementary feeding pattern and the nutritional status (weight-for-age) in infants at the age 7-12 months. Further research about other variables is needed.